Effects of high-protein high-fiber meal replacements on weight loss and dietary composition in overweight women: A randomized controlled trial - Nurwanti, Esti; Muhammad, Harry Freitag Luglio; Nguyen, Ngan Thi Kim; Nurdin, Naufal Muharam (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
ABSTRACTBackground: Energy deficit is essential for weight loss; however, an effective weight loss program should also focus on improving dietary composition.Objective: This study aims to evaluate the effects of high-protein, high-fiber dietary supplements on weight loss and body composition improvements in overweight individuals.Methods: This experimental study utilized a randomized controlled trial (RCT) design. Participants were women and were randomly assigned to either a control group or an intervention group. Criteria of this study are: Female aged 20-30 years; Body Mass Index (BMI) between 25 and 30 kg/m²; No allergies, including soy allergies; Fasting blood glucose level (FBG) < 100 mg/dL. The control group received 2 sessions of nutritional counselling by nutritionists to follow a low-calorie diet, while the intervention group received the same counselling along with a daily meal replacement containing 184 kcal energy, 17 grams of protein and 5 grams of dietary fiber.Results: After an 8-week weight loss program, participants in the intervention group experienced significantly greater weight loss (-3.4 ± 0.43 kg) compared to the control group (-2.4 ± 0.5 kg) (p = 0.047). Additionally, a higher proportion of participants in the intervention group (62%) achieved the 5% weight loss threshold compared to the control group (28%) (Chi-Square p = 0.033). The intervention group also showed improvements in macronutrient composition compared to control, with a greater reduction in fat intake (-7.1 vs 2.1, p = 0.013) and increased consumption of protein (5.9 vs 1.8, p = 0.002) and fiber (7.21 vs 4.26, p = 0.026).Conclusion: The use of high-protein, high-fiber meal replacements was associated with improvement of weight loss compared to standard low-calorie diet counselling alone.Keywords: Diet; meal replacement; obesity; weight loss